Holding and restraining children for clinical procedures: A scoping review of health professional reported and observed practice - da Silva, Ronaldo Antonio; Tordivelli, Rayssa Steiner [UNESP]; Garcia de Avila, Marla Andréia [UNESP]; Bray, Lucy; Ferraz de Almeida, Graziela Maria [UNESP]; Francisco, Janaina Chinaque [UNESP]; Gaíva, Maria Aparecida Munhoz (SAGE Publications, 2024)
Holding and restraining children during non-urgent clinical procedures continues to be surrounded by uncertainty and mired in controversy. This review aimed to locate, appraise and map the evidence related to health professionals reported and observed practice of holding and restraining children, from birth to 16 years, for clinical procedures. This scoping review, conducted in April 2022, was based on the Joanna Briggs Institute protocol. Screening and full text review resulted in the inclusion of 30 papers. In total, 14 different terms were used to refer to the act of holding or restraining a child for a procedure, in many papers the action of holding was not defined. Professionals report the main factors influencing their decisions to use restraint and/or holding were the age of a child, with younger children being restrained or held most frequently; a child’s behaviour; and concerns around a child’s safety. Professionals also report that they can perceive pressure from parent/carers to hold or restrain their child and describe how holding practices can be influenced by service and organisational pressures. Health professionals, mainly nurses, continue to report ethical and moral tensions linked to their involvement in the restraint or holding of a child against their will for a clinical procedure. Evidence indicates a need to move practice forward as the issues identified in paediatric practice are long-standing and historical.
Keywords: child rights; Clinical holding; paediatric nursing; physical; procedure; restraint